Case report: A rare but fatal complication of hysteroscopy—air embolism during treatment for missed abortion - Ou, Yang; Li, Jun-Qiang; Tang, Rong; Ma, Duo-Na; Liu, Yang (Frontiers in Medicine, 2024)
Hysteroscopic procedures complicated by air embolism (AE) are exceptionally rare occurrences in clinical practice, and there have been no previously reported cases of AE associated with hysteroscopic dilation and curettage. While the overall incidence of this complication is low, the consequences can be devastating. During early pregnancy, the unique physiological changes, such as elevated hormonal levels and increased uterine blood supply, significantly heighten the risk of AE development. Therefore, the prompt recognition of early signs and symptoms, coupled with the implementation of timely and effective interventions, are crucial to improve patient survival rates and minimize the risk of long-term sequelae. This case report presents the characteristic clinical manifestations and imaging findings associated with AE, providing a valuable clinical reference for obstetricians and gynecologists to recognize this rare yet potentially life-threatening complication of hysteroscopic procedures. Early detection and appropriate management are essential to optimize patient outcomes and prevent catastrophic consequences.